The Mathematical Problem-Solving Ability of Tadris Mathematics Students In Terms of Initial Ability - Palupi, Dini; Badeni, Badeni; April Yanti, Fitri (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Problem-solving skills are indispensable in 21st century learning. The rapid development of technology in the digital era demands the readiness of students to compete and face various problems that arise. These problems require skills in solving problems. This study aims to illustrate how the mathematical problem solving ability of students of the mathematics tadris study program is based on the initial ability of students. This research is a quantitative descriptive research, with the research subjects of mathematics tadris students totaling 15 people. The instruments used in this study were questionnaires, interviews, and documentation in the form of test questions and student answers. The results revealed that mathematical problem solving skills: a) high-ability students were good in all mathematical problem solving indicators and received satisfactory score scores; b) Moderately capable students mostly master 4 to 3 indicators of mathematical problem solving, but the final result of the question answers given by most students is correct; c) Low-ability students are mostly only able to master 2 to 3 indicators of mathematical problem solving, so many problems are solved incorrectly and even incorrectly. Researchers concluded that there are several characters of mastery of mathematical problem solving indicators at each level of students' initial abilities. Lecturers need to present learning methods that are able to accommodate so that students' mathematical problem solving skills can be developed optimally, in each student based on initial abilities.